Recent strategies toward microfluidic‐based surface‐enhanced Raman spectroscopy. Issue 16 (12th May 2017) - Tycova, Anna; Prikryl, Jan; Foret, Frantisek
Abstract : Surface‐enhanced Raman spectroscopy (SERS) is an extremely powerful analytical tool, which not only yields information about the molecular structure of the analyte in the form of characteristic vibrational spectrum but also gives sensitivities approaching those in fluorescence spectroscopy. The SERS measurement on the microfluidic platform provides possibility to manufacture the device with design perfectly fulfilling the needs of the application with minimal sample consumption. This review aims at describing basic strategies for SERS measurement in microfluidic devices published in the last decade and covers current trends in microfluidics with SERS detection in the field of bioanalysis and approaches toward on‐line coupling of liquid‐based separation techniques with SERS detection.